Digital Transformation of Banking and Its Legal Risks - Muhamad Agung Dharmajaya (Jurnal Ekonomi, 2022)
Digital transformation of banking through the adoption of cutting-edge technology offers high efficiency, but on the other hand, it triggers the emergence of regulatory asymmetry (regulatory lag) and various new risk variants. This study aims to identify the dominant legal risk typologies in the era of banking digitalization and evaluate the readiness of the regulatory framework and effective legal risk mitigation mechanisms. The research method used is normative juridical with a descriptive-analytical approach to examine primary, secondary, and tertiary legal materials through literature review, which are then analyzed qualitatively using deductive reasoning. The results indicate three main legal risk typologies: violations of personal data protection due to data breaches, escalation of cybercrime such as phishing and ransomware that trigger disputes over unauthorized transactions, and legal uncertainty regarding the validity of electronic contracts (e-contracts) and the reliability of digital evidence in court. This study concludes that banks can no longer rely on unilateral exoneration clauses that harm consumers. Legal mitigation efforts must be implemented holistically by strengthening internationally standardized information technology governance (ISO 27001), strengthening e-KYC systems, implementing standard digital forensics audit logs, and utilizing cyber insurance. Meanwhile, regulatory authorities are required to shift their policy approach to principle-based, adaptive regulation to create a secure, trustworthy, and legally certain digital banking ecosystem.